Anthropometric, speed and endurance characteristics of English academy soccer players: Do they influence obtaining a professional contract at 18 years of age? - Emmonds, S.; Till, K.; Jones, B.; Mellis, M.; Pears, M. (International Journal of Sports Science & Coaching, 2016)
This study evaluated the anthropometric, speed and endurance characteristics of English academy soccer players, comparing players who obtained a `professional` contract at 18 years old with those that did not (`academy`); 443 male academy soccer players from an English professional club undertook anthropometric (height and body mass), speed (10 and 20m sprint) and endurance (Yo-Yo intermittent endurance test level 2 [Yo-Yo]) assessments between 2005 and 2012. Significant improvements with age were found for speed and endurance at each annual age group up until U18 age category. Significant differences were only observed between `professional` and `academy` players for 10m (p=0.003, 2=0.01) and 20m (p=0.001, 2=0.01) speed at U16 and U18 and Yo-Yo performance (p=0.001, 2=0.12) at U18 age category. Practitioners should use speed and endurance assessments for monitoring physical development of players rather than for talent identification purposes.